In Vivo Evaluation of Physiologic Control Algorithms for Left Ventricular Assist Devices Based on Left Ventricular Volume or Pressure. Issue 5 (September 2017) - Ochsner, Gregor; Wilhelm, Markus J.; Amacher, Raffael; Petrou, Anastasios; Cesarovic, Nikola; Staufert, Silvan; Röhrnbauer, Barbara; Maisano, Francesco; Hierold, Christofer; Meboldt, Mirko; Schmid Daners, Marianne
Abstract : Turbodynamic left ventricular assist devices (LVADs) provide a continuous flow depending on the speed at which the pump is set, and do not adapt to the changing requirements of the patient. The limited adaptation of the pump flow (PF) to the amount of venous return can lead to ventricular suction or overload. Physiologic control may compensate such situations by an automatic adaptation of the PF to the volume status of the left ventricle. We evaluated two physiologic control algorithms in an acute study with eight healthy pigs. Both controllers imitate the Frank–Starling law of the heart and are based on a measurement of the left ventricular volume (LVV) or pressure (LVP), respectively. After implantation of a modified Deltastream DP2 blood pump as an LVAD, we tested the responses of the physiologic controllers to hemodynamic changes and compared them with the response of the constant speed (CS) mode. Both physiologic controllers adapted the pump speed (PS) such that the flow was more sensitive to preload and less sensitive to afterload, as compared with the CS mode. As a result, the risk for suction was strongly reduced. Five suction events were observed in the CS mode, one with the volume-based controller and none with the pressure-based controller. The results suggest that both physiologic controllers have the potential to reduce the number of adverse events when used in the clinical setting. Abstract : Supplemental Digital Content is available in the text.